Kejahatan dalam Perspektif Filsafat Proses Whitehead - Joko Siswanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2000)
The purpose of this research is to inventory, describes, and critical analysis the nature evil of Whitehead's Process Philosophy.This research is pure library study. Data are collected from Whitehead's works. Philosophical-hermeneutics is usen in this research, namely, descriptive, comparative, and reflective.The results of this research are as follows:1. Evil is not